Making Monetary Policy More Effective : The Case of the Democratic Republic of the Congo - Fischer, Felix (IMF Working Papers; Working Paper ;, 2013)
The paper looks at the challenges of conducting monetary policy in a context of high dollarization of the banking system and weak institutions in the Democratic Republic of the Congo. The empirical analysis confirms the limited effectiveness of the Central Bank of Congo in controlling inflation, despite a rapid policy response to inflation shocks. Options available to enhance the effectiveness of monetary policy are limited. After exploring the pros and cons of different exchange regimes we conclude that strengthening the current monetary policy framework remains the first-best option, given the country's exposure to frequent terms-of-trade shocks.